2011
DOI: 10.2174/1875934301104010001
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Body Mass on Whole-Body Vibration: A Quad-Bike Field Study

Abstract: Objectives: The aim of this field study was to explore the relationship between body mass and quad bike induced whole-body vibration (WBV) exposure in a group of New Zealand rural workers. Methods: WBV exposure was recorded using a seat pad mounted tri-axial accelerometer while rural workers (n=34) were driving a quad bike for approximately half an hour on a pre-marked track on farm terrain. Personal factors such as age, height and quad bike driving experience were also surveyed and included as co-variates. Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…It should be noted that this was in agreement with the high prevalence of low and upper back pain (64.3%), pain in lower and upper limbs, and elbows (shoulders, forearm, elbows, wrist, hand and fingers, knees, legs, and feet; 67.9%), presence of a disease (50%), and regular alcohol consumption (64.3%) which were revealed by a supplementary analysis on the study operators. The finding in our study that body weight was not a significant predictor for WBV is in agreement with the result of a study among rural workers driving quad bikes [39] . It is in contrast to the result of a study in urban taxi drivers which reported a relationship between a driver's body weight and WBV exposure [37] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It should be noted that this was in agreement with the high prevalence of low and upper back pain (64.3%), pain in lower and upper limbs, and elbows (shoulders, forearm, elbows, wrist, hand and fingers, knees, legs, and feet; 67.9%), presence of a disease (50%), and regular alcohol consumption (64.3%) which were revealed by a supplementary analysis on the study operators. The finding in our study that body weight was not a significant predictor for WBV is in agreement with the result of a study among rural workers driving quad bikes [39] . It is in contrast to the result of a study in urban taxi drivers which reported a relationship between a driver's body weight and WBV exposure [37] .…”
Section: Discussionsupporting
confidence: 93%
“…In addition to this a job-associated factor can also be thought of which includes road condition, task design, work organization, and working condition [35] , [36] , [37] , [38] . Previous studies on professional drivers of forklift trucks, forestry machines, mobile cranes, trucks, tractors, subway trains, and harvesters have shown that their WBV exposure was influenced by a number of personal and physical factors including posture, workplace and vehicle characteristics (road condition, suspension systems, seat type, load, and maintenance of vehicle) as well as driving experience, driving speed, and body mass index [26] , [33] , [36] , [37] , [38] , [39] , [40] . The results of an earlier study on WBV exposure by the truck operators indicated that among several factors such as seat type, driver experience, road condition, truck type, and truck mileage, only the truck type and road condition are the factors that significantly influence the WBV exposure level [38] .…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study shows similar circumstance with previous studies by Blood et al [28] who "…demonstrated a casual observation to significant negative association between body mass and vibration exposure." However, another study mentioned that "body mass is significantly associated with quad bike induced WBV in a group of New Zealand rural workers" [29]. Different results may occur and are influenced by different research objects and environment conditions.…”
Section: Vibration Exposure On Laborsmentioning
confidence: 99%
“…In these studies, the speed of vehicles was found to be a contributing factor to WBV exposure. Some studies found evidence that personal factors such as age and weight of operators were significant contributing factors to vibration magnitude measured at the seat [32][33]. A few studies have also found evidence of machinerelated factors influencing WBV [14,34].…”
Section: Introductionmentioning
confidence: 99%